1992
DOI: 10.1002/ps.2780340307
|View full text |Cite
|
Sign up to set email alerts
|

The use of ecotoxicological risk assessment in deriving maximum acceptable half‐lives of pesticides

Abstract: Approaches in ecological risk assessment are usually based on estimating the probability that organisms will be exposed to environmental concentrations of chemicals greater than some toxicological criterion (LC50, NOEC). Following this approach, quality standards for persistent chemicals in soil can be derived. For readily degradable chemicals emitted at intervals, the ecological risk can be related to the time taken for the chemical concentration to fall to a level causing no effect on most, e.g. 95%, of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…One approach to predict the likely recovery of a system is based on the dissipation half‐life of the compound, the initial exposure concentration and the hazardous concentration for 5% of species 65. If recovery is required within a year after a single application, then the chemical's half‐life should meet the condition: where T 1/2 is measured in years, C 0 is the initial concentration and HC 5 is the hazardous concentration for 5% of species.…”
Section: System Recoverymentioning
confidence: 99%
“…One approach to predict the likely recovery of a system is based on the dissipation half‐life of the compound, the initial exposure concentration and the hazardous concentration for 5% of species 65. If recovery is required within a year after a single application, then the chemical's half‐life should meet the condition: where T 1/2 is measured in years, C 0 is the initial concentration and HC 5 is the hazardous concentration for 5% of species.…”
Section: System Recoverymentioning
confidence: 99%
“…Reproduction rate is an especially important parameter for a species that allocates a great amount of resources to reproduction (van Straalen et al, 1992). Collembolans are an example of a species group that usually has high fecundity.…”
Section: Introductionmentioning
confidence: 99%
“…Van Rijn et al (1993) and Van Straalen et al (1992) have suggested a simple model to incorporate the above mentioned arguments in an ecotoxicological risk assessment for pesticides in soil. Degradation of the toxicant is assumed to follow a simple exponential decay process, characterized by a half-life DT50 (in days).…”
Section: Potential For Ecological Recoverymentioning
confidence: 98%